"Sublime Communion": The Theology of the Natural World in Laudato Si'. (June 2016) - Edwards, Denis
Laudato Si' offers a profound and in some respects new theology of the natural world. In the analysis offered here, it is proposed that three threads can be discerned in the theology of nature contained in Laudato Si ': first, other creatures have intrinsic value; second, they express and reveal God; third, they form with human beings a sublime communion of creation in God. The article concludes with a brief theological reflection on a theological development of the concept of sublime communion.